Tissue Biomarkers in Predicting Response to Sunitinib Treatment of Metastatic Renal Cell Carcinoma - Trávníček, Ivan; Branžovský, Jindřich; Kalusová, Kristýna; Hes, Ondřej; Holubec, Luboš; Pele, Kevin Bauleth; Ürge, Tomáš; Hora, Milan (Anticancer research, 2015)
AIM: To identify tissue biomarkers that are predictive of the therapeutic effect of sunitinib in treatment of metastatic clear cell renal cell carcinoma (mCRCC). MATERIALS AND METHODS: Our study included 39 patients with mCRCC treated with sunitinib. Patients were stratified into two groups based on their response to sunitinib treatment: non-responders (progression), and responders (stable disease, regression). The effect of treatment was measured by comparing imaging studies before the initiation treatment with those performed at between 3rd and 7th months of treatment, depending on the patient. Histological samples of tumor tissue and healthy renal parenchyma, acquired during surgery of the primary tumor, were examined with immunohistochemistry to detect tissue targets involved in the signaling pathways of tumor growth and neoangiogenesis. We selected mammalian target of rapamycine, p53, vascular endothelial growth factor, hypoxia-inducible factor 1 and 2 and carbonic anhydrase IX. We compared the average levels of biomarker expression in both, tumor tissue, as well as in healthy renal parenchyma. Results were evaluated using the Student's t-test. RESULTS: For responders, statistically significant differences in marker expression in tumor tissue versus healthy parenchyma were found for mTOR (4%/16.7%; p=0.01031), p53 (4%/12.7%; p=0.042019), VEGF (62.7%/45%; p=0.019836) and CAIX (45%/15.33%; p=0.001624). A further significant difference was found in the frequency of high expression (more than 60%) between tumor tissue and healthy parenchyma in VEGF (65%/35%; p=0.026487) and CAIX (42%/8%; p=0.003328). CAIX was expressed at high levels in the tumor tissue in both evaluated groups. CONCLUSION: A significantly higher expression of VEGF in CRCC in comparison to healthy parenchyma can predict a better response to sunitinib.
Keywords: dospělí; ledviny; nádorové biomarkery; nádory ledvin; indoly; Prognosis; senioři nad 80 let; studie případů a kontrol; Biomarkers, Tumor; Sunitinib; Humans; staging nádorů; Carcinoma, Renal Cell; Tissue Array Analysis; následné studie; lidé středního věku; Kidney Neoplasms; Antineoplastic Agents; Aged, 80 and over; Middle Aged; Neoplasm Staging; stupeň nádoru; Indoles; karcinom z renálních buněk; míra přežití; prediction; protinádorové látky; prognóza; Follow-Up Studies; biomarkers; mužské pohlaví; Survival Rate; immunohistochemistry; Adult; Metastatic renal carcinoma; Pyrroles; targeted-therapy; lymfatické metastázy; pyrroly; sunitinib; čipová analýza tkání; Lymphatic Metastasis; ženské pohlaví; Neoplasm Grading; Kidney; lidé; Case-Control Studies; imunoenzymatické techniky; Aged; senioři; Male; Immunoenzyme Techniques; Female